KEMAMPUAN MENULIS PUISI SISWA KELAS X SMK NEGERI 2 PONTIANAK TAHUN PELAJARAN 2018/2019 - Siti Ayu Fitria; Antonius Totok Priyadi; Syambasril Syambasril (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2019)
AbstractThis study aims to describe students’ writing ability based on the elements of poetry, including diction, image, concrete words, language styles, rhymes, typography, theme, sense, intonation, and message. This is qualitative research on the 10th-grade students of SMKN 2 Pontianak using the descriptive method. Data were collected using test, of which the data were analyzed using a descriptive statistics data analysis technique. The finding showed that the poetry writing ability based on 1) diction, 50 passed the test with the average score by 84,12 and percentage of completeness by 79,36%; 2) image, 45 passed with average by 87,82 and completeness by 71,42%; 3) concrete words, 50 passed with average by 91 and completeness by 70,36%; 4) language styles, 9 passed with average by 38,09 and completeness by 14,28%; 5) rhymes, 29 passed with the average 63,49 and completeness by 46,03%; 6) typography, 58 passed with the average 92,06 and completeness by 92,06%; 7) theme, all passed with an average 100 and completeness 100%; 8) senses, 42 missed with average by 74,20 and completeness by 66,66%; 9) intonation, all passed with average by 100 and completeness by 100%; and 10) Messages, all passed with average by 100 and completeness by 100%.Keywords: Poetry, Writing Skills, Writing Ability, Poetry Writing.